THE DEVELOPMENT OF REGIONAL AVIATION IN THE RUSSIAN FEDERATION - I. P. Zheleznaja (Научный вестник МГТУ ГА)
The article describes the problems of development of regional air transportation in the Russian Federation, the main difference of air transport from other transport modes, the reasons that led to the destruction of the existing system of regional flights, the basic functions of regional airports, proposals on the development of regional aviation.